Multiple sclerosis-related fatigue and possibilities of its correction - N. Yu. Lashch (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2016)
Multiple sclerosis (MS)-related fatigue is encountered in 75–92% of patients and it is one of the key symptoms that affect quality of life. Physicians and patients' relatives frequently underestimate MS-related fatigue; the latter may occur at any disease stage, its degree is inadequate to physical exercise and reduces after a short-term daytime rest. Fatigue due to MS is not directly related to the degree of paresis; however, it is more common in patients with pyramidal insufficiency. Overfatigue may be the first symptom of an MS exacerbation. The genesis of fatigue in MS is not known with certainty. The development of this symptom is associated with impairments in neuroimmune responses and biochemical processes and with the administration of some drugs. Special tests and scales are used to objectify the degree of fatigue. The most commonly used questionnaires are the Fatigue Severity Scores to rate physical and mental fatigue, as well as the Modified Fatigue Impact Scale in patients having MS. When a patient with MS complains about fatigue, it is necessary to rule out its other possible causes and to specify its relation to MS and the necessity of fatigue correction. Аmantadine is one of the drugs used for the symptomatic therapy of MS. This paper presents the data of randomized clinical trials evaluating the efficacy and safety of this drug for the symptomatic treatment of MS. Correction of MS-related fatigue requires a multidisciplinary approach that involves a combination of drug therapy, therapeutic exercises, active lifestyle, and relatives' understanding.